Computational Screening of Rheum palmatum Phytochemicals as Potential Anti-Diabetes Agent via Sodium-Glucose Transport Protein 2 Inhibition - Putra, Wira Eka; Sustiprijatno; Hidayatullah, Arief; Widiastuti, Diana; Fikri Heikal, Muhammad (Science & Technology Asia, 2024)
Diabetes mellitus is a debilitating condition that affects people all over the world. Diabetes mellitus can be brought on by a number of different factors, the most common of which include being overweight and leading an unhealthy lifestyle. There have been a number of attempts made to cure diabetes, however these therapies are not precise and can cause adverse reactions. The quest for novel pharmaceuticals derived from plants with therapeutic properties is something that really has to be done in order to cut down on the use of synthetic drugs and the negative consequences that come along with them. In light of this, the purpose of this research was to investigate the potential of the bioactive molecules of Rheum palmatum to serve as an anti-diabetic therapeutic candidate by inhibiting Sodium Glucose Transport Protein 2. Computational prediction consisting of protein and ligand optimization, molecular docking, and visualization was applied in this study. The generation of therapeutic candidates from the bioactive chemicals in R. palmatum showed promise based on computational analysis. In comparison to the control medication, the physcion8-glucoside, laccaic acid, chrysophanol, rhein, and aloe emodin showed reduced binding affinity scores. When compared to the standard anti-diabetic medicine, the binding location and other physicochemical parameters following molecular docking produced excellent and competitive results.